2014
DOI: 10.1093/arclin/acu070
|View full text |Cite|
|
Sign up to set email alerts
|

RBANS Embedded Measures of Suboptimal Effort in Dementia: Effort Scale Has a Lower Failure Rate than the Effort Index

Abstract: The importance of evaluating effort in neuropsychological assessments has been widely acknowledged, but measuring effort in the context of dementia remains challenging due to the impact of dementia severity on effort measure scores. Two embedded measures have been developed for the repeatable battery for the assessment of neuropsychological status (RBANS; Randolph, C., Tierney, M. C., Mohr, E., & Chase, T. N. (1998). The repeatable battery for the assessment of neuropsychological status (RBANS): Preliminary cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It is likely that some of the variation in performance seen across the different studies may be partially accounted for not just by dementia severity but by dementia subtype. Burton et al (2015) touched on this issue when they found that the Effort Scale had significantly higher specificity in their Alzheimer's sample (96%) compared to their non-Alzheimer sample (69%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that some of the variation in performance seen across the different studies may be partially accounted for not just by dementia severity but by dementia subtype. Burton et al (2015) touched on this issue when they found that the Effort Scale had significantly higher specificity in their Alzheimer's sample (96%) compared to their non-Alzheimer sample (69%).…”
Section: Discussionmentioning
confidence: 99%
“…The paper scored poorly however on the CCAT (21/40) due to inadequate information given regarding data collection, inclusion and exclusion criteria and participant demographic information. Burton, Enright, O'Connell, Lanting & Morgan (2015) compared the ES in AD and non-AD dementias. They found an impressively high specificity level of 0.96 in their AD sample, however this fell to 0.69 in their non-AD sample.…”
Section: Test Of Memorymentioning
confidence: 99%
“…Numerous research studies have been conducted regarding the ability of the measure to identify cognitive change in individuals with normal cognition (Andreotti & Hawkins, 2015; Cooley et al, 2015; Duff & Ramezani, 2015; Phillips et al, 2015; Thaler, Hill, Duff, Mold, & Scott, 2015), Mild Cognitive Impairment (MCI; Clark, Hobson, & O’Bryant, 2010; Duff, Hobson, Beglinger, & O’Bryant, 2010; Hobson, Hall, Humphreys-Clark, Schrimsher, & O’Bryant, 2010; Karantzoulis, Novitski, Gold, & Randolph, 2013; O’Mahar et al, 2012), and Alzheimer’s disease (AD; Burton, Enright, O’Connell, Lanting, & Morgan, 2015; Duff et al, 2008; Enright, O’Connell, MacKinnon, & Morgan, 2015; Heyanka, Scott, & Adams, 2015; McDermott & DeFilippis, 2010; Morgan, Linck, Scott, Adams, & Mold, 2010; Schmitt et al, 2010). Despite these efforts, however, there have been few studies examining the RBANS and its association with imaging biomarkers related to AD, such as decreased hippocampal volumes on magnetic resonance imaging (MRI; Choi et al, 2016; Jack et al, 2010), hypometabolism on fluoro-2-deoxyglucose (FDG) positron emission tomography (PET; Frings, Spehl, Hull, & Meyer, 2016; Jagust et al, 2010), and amyloid accumulations on amyloid PET (Beach, Thal, Zanette, Smith, & Buckley, 2016; L.…”
Section: Introductionmentioning
confidence: 99%
“…That is, due to a one or a combination of several potential factors (e.g., fatigue, apathy, distraction, boredom, intoxication), participants' scores do not reflect their true ability. This is different from feigned effort , in which performance is intentionally deficient with the goal of appearing cognitively impaired, although suboptimal effort has previously been used synonymously with feigned effort 16-18 . Feigned effort is a well-documented phenomenon in several patient populations, generally in the context of forensic or disability evaluations in which there is potential for secondary gain 19-22 .…”
Section: Introductionmentioning
confidence: 99%